PENGARUH EVALUASI PEMBELAJARAN TERHADAP MOTIVASI BELAJAR MATEMATIKA SISWA PADA SMP PGRI 2 CIAWI KABUPATEN BOGOR - Rifani Priharyanti; Hendro Prasetyono (STKIP Subang, 2025)
Education is a fundamental pillar in building the civilization of a nation, and its quality is reflected in the success of the learning process in achieving its intended goals. Among the essential subjects that cultivate logical, systematic, critical, and analytical thinking is Mathematics. These skills are vital in addressing the challenges of globalization, which demand complex problem-solving abilities. However, in practice, Mathematics is often perceived as a difficult and less engaging subject by students, leading to low learning motivation. This study aims to examine the influence of learning evaluation on students’ motivation to learn Mathematics at SMP PGRI 2 Ciawi, Bogor Regency. The hypothesis proposed in this study states that there is a significant relationship between learning evaluation and students’ motivation in learning Mathematics. A descriptive quantitative method was employed, using the Product Moment correlation analysis technique. The population consisted of all eighth-grade students at SMP PGRI 2 Ciawi, Bogor Regency, totaling 98 students. The results revealed a positive and significant correlation between learning evaluation and students’ motivation to learn Mathematics, with a correlation coefficient of r = 0.345, where r-count (0.345) > r-table (0.195) at a 5% significance level. This finding indicates that the better the learning evaluation is implemented, the higher the students’ motivation to learn Mathematics